Closure: An Appropriated Technique in Malay Absurd Plays: (Pengakhiran Cerita: Suatu Teknik dalam Karya Teater Absurd Melayu) (Malay Literature, 2015)
The period of experimental theatre in the 1970s had brought a significant change in the history of modern Malay theatre. The plays that were produced and staged during this era had been categorized as absurd plays as they contained strong tendencies towards the application of the absurd theatre techniques. The most significant features of Western absurd plays would be that the play would end the way it begins; this cycle emphasizes the meaninglessness of life portrayed by the absurd playwrights. However, the scenario in Malaysia is different. Sensitive to the social and religious background of the Malays, these playwrights made adjustments to the typical absurd techniques common practised in the West. As opposed an ambivalent and dark end of the plays, Malay absurd playwrights tend to present a sense of hope through the closures presented at the end of the plays. Hence the theatre scholar, Solehah (1990) termed this as theatre absurd "ala" Malaysia as a way to characterize the unique version of the plays. This paper intends to delve further into the method of closure used by the playwrights such as Dinsman in his play, It Is Not A Suicide and the late Anuar Nor Arai's play, Vacuum. The closures in the two plays are perceived as bringing a ray of light for the Malay absurd plays from being dark and inappropriate in the history modern Malay theatre into today's popular eclectic mainstream that marked the end of the period of realistic plays.Keywords: absurd plays, closure technique, modern Malay drama, hope and realistic plays